2007
DOI: 10.1136/jnnp.200x.097923
|View full text |Cite|
|
Sign up to set email alerts
|

Cueing training in the home improves gait-related mobility in Parkinson's disease: the RESCUE trial

Abstract: Objectives: Gait and mobility problems are difficult to treat in people with Parkinson's disease. The Rehabilitation in Parkinson's Disease: Strategies for Cueing (RESCUE) trial investigated the effects of a home physiotherapy programme based on rhythmical cueing on gait and gait-related activity. Methods: A single-blind randomised crossover trial was set up, including 153 patients with Parkinson's disease aged between 41 and 80 years and in Hoehn and Yahr stage II-IV. Subjects allocated to early intervention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
667
6
15

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 753 publications
(707 citation statements)
references
References 41 publications
19
667
6
15
Order By: Relevance
“…This is the first study examining the effects of a virtual (or augmented) reality device for at-home use aimed at improving gait in patients with PD. A prior randomized crossover trial of an external cue training program provided at home by physiotherapists demonstrated small but significant improvements in the Posture and Gait Scale score, a composite of related UPDRS items (13-15 and 29-30) [7]. While that study was the first controlled trial that used a cueing device at home, it relied on an open-loop system with cueing parameters that needed separate adjustments to increase stride length and avoid festination and a training program led by a rehabilitation specialist.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the first study examining the effects of a virtual (or augmented) reality device for at-home use aimed at improving gait in patients with PD. A prior randomized crossover trial of an external cue training program provided at home by physiotherapists demonstrated small but significant improvements in the Posture and Gait Scale score, a composite of related UPDRS items (13-15 and 29-30) [7]. While that study was the first controlled trial that used a cueing device at home, it relied on an open-loop system with cueing parameters that needed separate adjustments to increase stride length and avoid festination and a training program led by a rehabilitation specialist.…”
Section: Discussionmentioning
confidence: 99%
“…Examples are fixed-velocity visual cues [5] or rhythmic auditory cues [6]. While open-loop stimulation may offer some benefit to some patients [3,7], such cues were found to cause confusion and exacerbate freezing of gait in others [3]. Indeed, it is well known that the stabilization of open-loop dynamic systems, which are inherently unstable, can only be achieved by feedback, that is closed-loop, systems [8].…”
Section: Introductionmentioning
confidence: 99%
“…[31]. Сходные данные получены в результате исследования эффективности ау-дио-и визуальной стимуляции [32].…”
Section: методы темпоритмовой коррекции ходьбы (тркх)unclassified
“…Ideally, there should be a balance between efficacy, safety and usefulness of a given intervention in order to be considered clinically useful and recommend for referral. However, regarding safety it has only been reported concerns on potential adverse effects of cueing-based gait training but it was shown not to increase the risk of falling 20 . Similarly, there has also been concerns of the possible adverse effects of nutritional supplements and its influence on antiparkinsonian medication 3 .…”
Section: To What End?mentioning
confidence: 99%